Institutional Basis of Social-Public Dialogue Modification in Contemporary Russia - Diana Taimurazovna Dzgoeva (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The main purpose of this article is associated with an attempt of theoretical understanding and comparative analysis of the existing models of interaction between government and society, and detection of the problems and the contradictions arising in the process of forming a social-public communication.